Kajian Literatur: Problematika dan Faktor Penyebab Rendahnya Pemahaman Bacaan Pada Siswa di Kelas Atas Sekolah Dasar - Ariana, Vira; Yasinta Mahendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension ability is a fundamental skill that determines the learning success of elementary school students because almost all subjects require understanding written information. This study aims to examine the forms of problems and the factors causing low comprehension of narrative texts through a literature review method. Data sources were obtained from national scientific journal articles traced through Google Scholar and indexed journal portals with a publication range from 2017 to 2025. The results of the review indicate that most students are able to read fluently but are not yet able to understand the meaning of the text as a whole. Students experience difficulties in identifying the main idea, retelling the text, understanding story elements, drawing conclusions, and answering inferential questions. This condition shows that students’ reading ability is still at the decoding stage and has not yet reached the stage of constructing meaning. The contributing factors include limited vocabulary, low reading interest, instruction that has not applied comprehension strategies, and a literacy environment that is not sufficiently supportive. Therefore, reading instruction is needed that emphasizes comprehension strategies, vocabulary enrichment, and sustained literacy habits.